1996
DOI: 10.1128/aem.62.4.1151-1158.1996
|View full text |Cite
|
Sign up to set email alerts
|

The ligninolytic system of the white rot fungus Pycnoporus cinnabarinus: purification and characterization of the laccase

Abstract: The white rot fungus Pycnoporus cinnabarinus was characterized with respect to its set of extracellular phenoloxidases. Laccase was produced as the predominant extracellular phenoloxidase in conjunction with low amounts of an unusual peroxidase. Neither lignin peroxidase nor manganese peroxidase was detected. Laccase was produced constitutively during primary metabolism. Addition of the most effective inducer, 2,5-xylidine, enhanced laccase production ninefold without altering the isoenzyme pattern of the enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
205
3
14

Year Published

1998
1998
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 673 publications
(239 citation statements)
references
References 50 publications
(40 reference statements)
17
205
3
14
Order By: Relevance
“…The laccase activity was 50% inhibited by 1 mM hydroxyquinoline but not by 1 mM EDTA like the enzymes of Trametes sanguinea [22] and Pycnoporus coccineus [25]. The enzyme was inactivated by either 1 mM cysteine, 1 mM mercaptoethanol or 1 mM sodium azide as observed with other fungal enzymes [21,22]. Copper atoms participate in the catalysis and dithiocarbamate, a speci¢c copper chelator, inactivated the exolaccase activity of T. terrestris only at 7.5 mM, suggesting that the copper atom might be inaccessible to the chelator.…”
Section: Enzyme Characterizationmentioning
confidence: 65%
See 1 more Smart Citation
“…The laccase activity was 50% inhibited by 1 mM hydroxyquinoline but not by 1 mM EDTA like the enzymes of Trametes sanguinea [22] and Pycnoporus coccineus [25]. The enzyme was inactivated by either 1 mM cysteine, 1 mM mercaptoethanol or 1 mM sodium azide as observed with other fungal enzymes [21,22]. Copper atoms participate in the catalysis and dithiocarbamate, a speci¢c copper chelator, inactivated the exolaccase activity of T. terrestris only at 7.5 mM, suggesting that the copper atom might be inaccessible to the chelator.…”
Section: Enzyme Characterizationmentioning
confidence: 65%
“…The expression of laccase in T. terrestris was regulated by a low C/N ratio in spite of the growth rate. High C/N ratios increased the production of laccase in Pycnoporus cinnabarinus [21] whereas in Lentinus edodes [24], Phanerochaete chry-soporium [6] and Phanerochaete £avido-alba [7] the opposite was observed.…”
Section: Physiology Of Laccase Productionmentioning
confidence: 88%
“…Enzyme extraction of the solid medium and assay of laccase PPO-I activity showed that laccase production increased as the concentration of veratryl alcohol in the solid media increased up to 20 Wmol g 31 substrate ( Table 1). Several basidiomycetes are known to produce veratryl alcohol, albeit at low levels [4], which induced laccase production [8]. Pleurotus spp.…”
Section: Mycelial Growth On Solid Media In the Presence Of Veratryl Amentioning
confidence: 99%
“…The chief function of veratryl alcohol is as a redox mediator between LiP and lignin degradation [6], and in protecting LiP during the redox cycle from metabolically produced H 2 O 2 [7]. It can also act as an inducer of laccases in basidiomycetes [8] and ascomycetes [9], and hence promote lignocellulose degradation.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies suggest that in white-rot fungi the combination of laccase with either lignin peroxidase and/or manganese peroxidase are responsible for the lignin degradation. In the strain Pycnoporus cinnabarinus I-937 (ATCC 200478) neither lignin peroxidase nor manganese peroxidase were detected in lignin degradation conditions [4]. The blue multicopper oxidases, like laccases, are in the ascorbate oxidase and mammalian plasma ceruloplasmin family, which have been subjected to extensive biochemical and structural characterization [5].…”
mentioning
confidence: 99%